Предмет: Алгебра,
автор: IsenayHanako
Решить уравнение: lg(x-4)+lg(x+3)=lg(5x-4)
Ответы
Автор ответа:
0
ОДЗ
x > 4
lg(x-4)+lg(x+3)=lg(5x-4)
lg ((x - 4)*(x + 3)) = lg (5x - 4)
(x - 4) (x + 3) = 5x - 4
x^2 - x - 12 = 5x - 4
x^2 - 6x - 8 = 0
D = 36 + 4*8 = 36+32 = 68
x1 = ( 6 + 2√17)/2 = 3 + √17; ∈
x2 = ( 6 - 2√17)/2 = 3 - √17; ∉
ОТВЕТ:
3 + √17
x > 4
lg(x-4)+lg(x+3)=lg(5x-4)
lg ((x - 4)*(x + 3)) = lg (5x - 4)
(x - 4) (x + 3) = 5x - 4
x^2 - x - 12 = 5x - 4
x^2 - 6x - 8 = 0
D = 36 + 4*8 = 36+32 = 68
x1 = ( 6 + 2√17)/2 = 3 + √17; ∈
x2 = ( 6 - 2√17)/2 = 3 - √17; ∉
ОТВЕТ:
3 + √17
Автор ответа:
0
Большое спасибо за подробное решение.Вспоминаю алгебру потихоньку)
Похожие вопросы
Предмет: Английский язык,
автор: arthurisraelyan228
Предмет: Алгебра,
автор: odiwka
Предмет: Английский язык,
автор: plz1731
Предмет: Математика,
автор: suptrarina2003